Pengaruh Budaya Organisasi terhadap Penciptaan Perilaku Inovatif dalam Meningkatkan Kinerja Organisasi Publik - Edward, Aurelia Valentin; Frinaldi, Aldri (Medan Resource Center, 2024)
This study examines the role of organizational culture in fostering innovative behavior within public organizations. The context highlights the increasing necessity for public entities to adapt and innovate in response to evolving societal needs and challenges. The research question addresses how specific cultural attributes within these organizations influence employees' propensity to engage in innovative behaviors. Utilizing a mixed-methods approach, the study combines quantitative surveys with qualitative interviews to gather comprehensive data from various public sector employees. The findings reveal that a supportive culture characterized by openness, trust, and encouragement of risk-taking significantly enhances innovative behavior. Additionally, leadership practices that model and reward innovation further strengthen this relationship. The conclusion posits that cultivating such a culture is essential for public organizations aiming to remain relevant and effective in a dynamic environment. The study underscores the critical role of organizational culture as a catalyst for innovation, suggesting targeted strategies for public sector leaders to foster an environment conducive to creative and progressive thinking.